2010
DOI: 10.1089/jwh.2009.1507
|View full text |Cite
|
Sign up to set email alerts
|

Postexertional Malaise in Women with Chronic Fatigue Syndrome

Abstract: The results of this study suggest that PEM is both a real and an incapacitating condition for women with CFS and that their responses to exercise are distinctively different from those of sedentary controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 37 publications
9
97
1
Order By: Relevance
“…include the onset of muscle weakness, muscle stiffness, pain, dizziness, headache and a flu-like malaise [8,15]. Depending on the nature and severity of the symptoms, patients can either stop and rest or change to an activity involving a different muscle group, or both [12].…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…include the onset of muscle weakness, muscle stiffness, pain, dizziness, headache and a flu-like malaise [8,15]. Depending on the nature and severity of the symptoms, patients can either stop and rest or change to an activity involving a different muscle group, or both [12].…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…recovery after challenging events [11,15]. Although a stressful activity may not precipitate an exacerbation of symptoms on the same day, it is advisable to spend the remaining hours doing less exhausting but meaningful tasks interspersed with periods of rest and relaxation [60].…”
Section: Symptom-contingent Pacingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that an activity limit exists in CFS, and that exercising above this can lead to an increase in some symptoms [8] . A Dutch survey (n = 100) found that 38% of CFS patients reported feeling worse following CBT [3] .…”
mentioning
confidence: 99%
“…CFS is associated with dozens of symptoms [7] , and exercise of various intensities has been shown to exacerbate numerous symptoms [8][9][10] . Many of these symptoms are not measured by the instruments that Heins et al used, suggesting that the claim that 'patients receiving CBT do not experience more frequent or more severe symptom deterioration than untreated patients' at best only applies to some of the symptoms individuals with CFS can experience.…”
mentioning
confidence: 99%